Erratum to: Low dose of chlorine exposure exacerbates nasal and pulmonary allergic inflammation in mice (Scientific Reports, (2018), 8, 1, (12636), 10.1038/s41598-018-30851-6) - de Genaro I.S. (2018)
© 2018, The Author(s).The Acknowledgements section in this Article is incomplete. “This work was supported by Sao Paulo Research Foundation, (FAPESP) grant 2009/53904-9 and grant 2012/15165-2, Experimental Therapeutic Laboratory I (LIM 20), School of Medicine, University of Sao Paulo, School of Medicine Foundation (FFM/USP) and Financial Assistance to Educational Project or Research (AUXPE/PROAP) grant 2696/2013.” should read: “This work was supported by Sao Paulo Research Foundation, (FAPESP) grants 2009/53904-9, 2012/15165-2 and 2018/20380-6, Experimental Therapeutic Laboratory I (LIM 20), School of Medicine, University of Sao Paulo, School of Medicine Foundation (FFM/USP) and Financial Assistance to Educational Project or Research (AUXPE/PROAP) grant 2696/2013.”